Factors shaping young tourists' intentions to travel to Greece, Israel and Portugal: Universal or idisyncratic perceptions of young Greeks, Israelis and Portugese? - Shahrabani, S. (2021)
Tourism constitutes an important branch of economy, especially in countries experiencing economic crisis and harsh socio-political events. The current study compares the intention of young people from three different countries – Greece, Israel and Portugal - to travel to two selected destinations. For each country of origin the other two countries were the destination of interest. This research examined the factors affecting young tourists' intention to travel to different destinations assuming that those determinants depend on the country of origin as well as on the destination country. The sample comprised of 648 students: Israelis (277), Portuguese (200), Greeks (171). The research questionnaire was distributed in Israeli, Greek and Portuguese academic institutions in 2014. The results indicate that over half of the Israelis intend to visit Greece or Portugal. The majority of the Portuguese anticipate visiting Greece, while only 32.5% expect to visit Israel. Among the Greeks nearly 50% intend to visit Portugal and do not intend to visit Israel. The study showed that the main factors affecting the decisions of young Portuguese to travel to Israel were: the image of Israel, the perceived risk of traveling to a country with political unrest and the number of trips abroad. The main factors affecting the decisions of young Greeks were the perceived risk of traveling to a country with political unrest and Israel's image. Israelis' decision to travel to Greece was affected by their image of Greece; the Portuguese also took into account the perceived risk regarding economic situation. For Israelis, considering Portugal as a traveling destination was related to the destination's image. The Greeks were affected by the number of Facebook friends and the Innovation, Entrepreneurship and Digital Ecosystems perceived economic risk. This research suggests that the socio-economic, political context of the country of origin and of the tourist destination plays an important role in young tourists' travelling-related decision-making.